SPERM WHALE SURFACE ACTIVITY FROM TRACKING BY RADIO AND SATELLITE TAGS 1 - William A. Watkins; Mary Ann Daher; Nancy A. Dimarzio; Amy Samuels; Douglas Wartzok; Kurt M. Fristrup; Damon P. Gannon; Paul W. Howey; Romaine R. Maiefski; Trevor R. Spradlin (Marine Mammal Science, 1999)
A bstract Three 12‐m sperm whales ( Physeter catodon ) were tagged and tracked west of Dominica in the southeast Caribbean to follow the surfacing patterns and movements of these presumed subadult males. Whale N was tagged in April 1993 with a 30‐MHz radio tag and tracked for two days. Whale H was tagged in April 1995 with a 30‐MHz radio tag and tracked for 4.6 d. Whale A was tagged in April 1995 with a satellite‐monitored tag tracked by ARGOS for 21.5 d, the first four of which were concurrent with the tracking of Whale H, an associate. The tagged whales remained west of Dominica for at least 2, 5, and 13 d, respectively. Whales N and A then moved southward to waters off Martinique. There were no apparent effects on the whales by tagging or the presence of the tags. The whales averaged speeds of 2.6‐3.5 km/h. Surfacings, indicated by tag signals, were of two types: short surfacings apparently primarily for respiration, averaging 7‐10.5 min between repeated longer dives, occurring day and night; and extended surfacings seemingly for rest and social interactions with conspecifics, occurring mostly in daylight. Whales were near the surface for 20.4%–22.6% of the total time (26.6%–27.1% during the day and 14.9%–17.1% at night). Delayed blowing was observed as Whale N surfaced for 8.3 min between 47‐ and 45‐min dives but delayed the first of its 31 blows for 1.5 min after surfacing.